Prikaz dveh načinov krepitve skeletnih mišic z električno stimulacijo - Štefančič, Martin (Rehabilitacija (Ljubljana), 2011)
Background: Electrical stimulation is often used in rehabilitation medicine for strengthening skeletal muscles. However, in achieving optimal effects, many open questions remain regarding the protocols, conditions and, particularly, selection of parameters. Methods: Twenty healthy volunteers were divided into two study groups of 10 persons each. The first group underwent strengthening training of knee extensor muscles using electrical stimulation on both sides, while the second group used electrical stimulation on the dominant side and active exercise using biofeedback on the non-dominantside. Changes in muscular strength were assessed by measuring peaktorque of isometric knee extension. Additionally, blood serum electrolytes and basic biochemical serum parameters were analysed in the first group. In the first group, torque measurements were also compared with physical activity self-assessment scores. All the collected data were statistically analysed. Results: A statistically significant increase in peak torque of isometric contraction was observed in both groups on the dominant as well as on the non-dominant lower limb. The increase differed between the groups. It was statistically significantly larger in the second groups, whereby within that group it was larger on the non-dominant side, i.e., after active exercise using biofeedback. Blood test indicated an increase after training only in creatine kinase, but it was not statistically significant. Physical activity self-assessment scores correlated negatively with age and were only marginally significantly associated with some of the other measured parameters. Conclusion: Based on the literature and our own findings, we believe that electrical stimulation is viable as a supplementary method for muscle strengthening in addition to the main one, i.e., properly chosen therapeutic exercise.
Keywords: električna stimulacija; krepitev; progaste mišice; rehabilitacija; vaje; vocational rehabilitation